2018
DOI: 10.11648/j.ajns.20180704.15
|View full text |Cite
|
Sign up to set email alerts
|

The Nursing Research of Frozen Fresh Potato Topical Treatment Infusion Leakage

Abstract: Objective: Intravenous (IV) infusions are an essential part of hospital patient care, but Intravenous Infiltration in the process of the treatment. Leakage brought great pain to the patient; So far, no research has been done in this area. A simple and cheap method to relieve pain of IV infusions in this Study. Method: According to the accepted methods of treatment, all patients were divided into three groups randomly, Group A: Wash and dry the fresh potatoes. Group B:Apply the Hirudoid cream clockwise evenly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Phlebitis is an inflammation of the vein caused by chemical, mechanical, or infectious irritation (Gorski, 2017; Higginson & Parry, 2011). Several pharmacological interventions (e.g., nonsteroidal antiinflammatory drugs (NSAIDs) (Berardi et al, 2003), heparin (Ikeda, Douchi, & Nagata, 2004), steroid ointment (Hamabe et al, 2017), and traditional medicines such as Sesame indicum (Bigdeli Shamloo et al, 2019), Nigella sativa (Behnamfar, Parsa Yekta, Mojab, & Kazem Naeini, 2019), and potato (Zhang, Jin, & Wang, 2018)) have been suggested to help reduce incidence of infusion phlebitis and CIP. However, the number of evidences is limited and it is yet unknown what are the most efficient methods.…”
Section: Discussionmentioning
confidence: 99%
“…Phlebitis is an inflammation of the vein caused by chemical, mechanical, or infectious irritation (Gorski, 2017; Higginson & Parry, 2011). Several pharmacological interventions (e.g., nonsteroidal antiinflammatory drugs (NSAIDs) (Berardi et al, 2003), heparin (Ikeda, Douchi, & Nagata, 2004), steroid ointment (Hamabe et al, 2017), and traditional medicines such as Sesame indicum (Bigdeli Shamloo et al, 2019), Nigella sativa (Behnamfar, Parsa Yekta, Mojab, & Kazem Naeini, 2019), and potato (Zhang, Jin, & Wang, 2018)) have been suggested to help reduce incidence of infusion phlebitis and CIP. However, the number of evidences is limited and it is yet unknown what are the most efficient methods.…”
Section: Discussionmentioning
confidence: 99%
“…9 Zhang et al (2018) proved that topical fresh frozen potato chips can relieve the symptoms of infusion leakage, and greatly reduce the occurrence of phlebitis. 10 Guo et al (2020) demonstrated that potato sprays had certain anti-inflammation and detumescence effects in mice with chemotherapy-induced phlebitis. 11 Potato alkaloids are recognized to be the main effective ingredients for observed curative effects.…”
Section: Introductionmentioning
confidence: 99%